2002
DOI: 10.1310/fajf-7a8g-qar4-q0x5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of stavudine plus didanosine in asymptomatic HIV-infected children with plasma HIV RNA below 50,000 copies per milliliter

Abstract: Treatment with a dual combination of didanosine plus stavudine in naive children with nonadvanced HIV disease is safe and provides a satisfactory virological outcome at 1 year. Toxicity and drug resistance seem to occur rarely when this combination is used, which allows good adherence and spares other future treatment options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 30 publications
1
8
0
1
Order By: Relevance
“…This finding is in accordance with those of other reports that show the L74V mutation commonly occurs when didanosine is used alone but not when it is combined with other NRTIs [1,8,14]. However, in the children we describe, the high prevalence of HIV with NAMs would confer didanosine resistance.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…This finding is in accordance with those of other reports that show the L74V mutation commonly occurs when didanosine is used alone but not when it is combined with other NRTIs [1,8,14]. However, in the children we describe, the high prevalence of HIV with NAMs would confer didanosine resistance.…”
supporting
confidence: 93%
“…AZT, azidothymidineresistance mutations (NAMs); d4T, stavudine-resistance mutations (NAMs); 3TC, lamivudine-resistance mutations (M184V/I, E44D, and V118I); ABC, abacavir-resistance mutations (L74V, Y115F, and M184V); ddc, zalcitabine-resistance mutations (L74V and M184V); ddI, didanosine; and Q151M, the Q151M multidrug-resistance mutation. cohort were not different from the mutations in patients infected with HIV clades B, A, C, and F [1,8,10,15]. Disease status, growth (height and weight), CD4 cell percentage and cell count, HIV RNA level, and duration and types of NRTI regimens received did not predict the risk for the emergence of HIV with resistance, nor did they predict the degree of resistance.…”
Section: Figurementioning
confidence: 71%
See 1 more Smart Citation
“…In initial small pediatric [6, 7] and adult [8, 9] studies, d4T/ddI demonstrated good antiviral activity and was well tolerated. Subsequent larger studies of adults revealed that this combination, when compared with ZDV/3TC, was associated with a significantly increased rate of lactic acidosis, peripheral neuropathy, pancreatitis, lipodystrophy, and hepatitis [1015].…”
mentioning
confidence: 99%
“…In small pediatric studies, d4T/ddI has been shown to have virologic efficacy and was well tolerated [124,128]. However, in studies in adults, d4T/ddI-based combination regimens were associated with greater rates of neurotoxicity, hyperlactatemia and lactic acidosis, and lipodystrophy than therapies based on ZDV/3TC [129,130]; additionally, cases of fatal and non-fatal lactic acidosis with pancreatitis/hepatic steatosis have been reported in women receiving this combination during pregnancy [6,7].…”
Section: Choice Of Initial Antiretroviral Therapy (Tables 8-11) Genermentioning
confidence: 99%